An analysis Language Attitudes of the student in english education department UMN Al-washliyah - harahap, khairunnisa; nadila, Fasya; aulia, Najunda; Zulfitri (Pascasarjana Universitas HKBP Nommensen, 2024)
This study aims to analyze the language attitudes of students in the English Education Department at UMN Alwashliyah. Language attitude is an important factor in determining how students perceive and interact with the English language, which influences their learning experience and proficiency. The research was conducted using a qualitative-method approach, combining surveys and interviews with a sample of students from the department. The findings reveal that students have generally positive attitudes toward learning English, viewing it as essential for academic success and future career opportunities. However, there are also mixed feelings towards the use of English in social contexts, with some students expressing concerns about the pressure to speak fluently. The study highlights the importance of understanding language attitudes in shaping educational practices and suggests recommendations for enhancing English language teaching strategies in the department.